2023
DOI: 10.1002/cncr.34733
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1b study of pan‐AKT inhibitor vevorisertib alone or with paclitaxel or fulvestrant in PIK3CA/AKT/PTEN‐mutated advanced solid tumors

Abstract: Background:In this first-in-human phase 1b study (ClinicalTrials.gov identifier NCT02761694) of advanced solid tumors with PIK3CA/AKT/PTEN mutations, the authors investigated the safety and efficacy of the pan-AKT inhibitor vevorisertib (MK-4440; ARQ 751) as monotherapy or with paclitaxel or fulvestrant. Methods: Patients with histologically confirmed, advanced or recurrent, PIK3CA/ AKT/PTEN-mutated solid tumors, measurable disease according to Response Evaluation Criteria in Solid Tumors, version 1.1, and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…On the other hand, vevorisertib was evaluated in a Phase Ib study involving advanced solid tumors with PIK3CA/Akt/PTEN mutations, either as monotherapy or in combination with paclitaxel or fulvestrant. The trial results indicated a manageable safety profile and minimal to modest antitumor activity of vevorisertib, both alone and in combination with paclitaxel, in patients who had previously received treatment for advanced solid tumors with PIK3CA/Akt/PTEN mutations . Due to business reasons, the development of vevorisertib has been officially terminated (NCT02761694).…”
Section: Allosteric Akt Inhibitorsmentioning
confidence: 99%
“…On the other hand, vevorisertib was evaluated in a Phase Ib study involving advanced solid tumors with PIK3CA/Akt/PTEN mutations, either as monotherapy or in combination with paclitaxel or fulvestrant. The trial results indicated a manageable safety profile and minimal to modest antitumor activity of vevorisertib, both alone and in combination with paclitaxel, in patients who had previously received treatment for advanced solid tumors with PIK3CA/Akt/PTEN mutations . Due to business reasons, the development of vevorisertib has been officially terminated (NCT02761694).…”
Section: Allosteric Akt Inhibitorsmentioning
confidence: 99%
“…Vevorisertib (ARQ751) is another novel pan-AKT inhibitor that was investigated in preclinical studies as a single agent or in combination with sorafenib in hepatocellular carcinoma in cirrhotic rat models [215]. It was first evaluated in a phase Ib study as a single agent or in combination with paclitaxel or fulvestrant in PIK3CA/AKT/PTENmutated advanced solid tumors and demonstrated only modest clinical activity (5% in the monotherapy group and 20% ORR in the vevorisertib-paclitaxel group) [216].…”
Section: Akt Inhibitorsmentioning
confidence: 99%